PENGARUH KEPEMIMPINAN, MOTIVASI DAN KEMAMPUAN KERJA PEGAWAI NEGERI SIPIL DINAS KETENAGA KERJA, TRANSMIGRASI DAN KEPENDUDUKAN PROVINSI RIAU - Erikka Darma Putra; Marnis Marnis; Ahmad Rifqi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this study was tortment of determine the effect of leadership, employee motivation and ability Civil Affairs Departmen of Labour jobs, Transmigration and Population Riau Province totaling 269. While the sampling technique with the formula proposed by Slovin thus obtained of 73 people. Data analysis using multiple linear regression with SPSS 20.o rocks. Pursuant to the results of data analysis known that the leadhership, motivation and ability to work simultaneously and partially significant effect on the peformance of the Departmen of Employment civil servants work, Transmigration and Population of Riau Province. The large number of such influence is 78%. It is suggested to the Departmen of Employment Labor, Transmigration and Population of Riau province, need to be developed to create a sort of inductive reasoning logically it duties employed, so that an employee is able to actualize capabilities. Need to provide motivation in the form of reward (award) in the form of personal attention, praise for the achievement so that employess can always try to run the job. Need to improve the pevormance of employess at the Departmen of Employment Labour, Transmigration and Population of Riau Province, employers need to make efforts to improve the quality of work. So that employess can be required to work well.Keywords:Leadership, Motivation and Work Capabiliy and Performen